2013
DOI: 10.35784/bud-arch.2173
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary identification and evaluation of parameters affecting the capacity of the operator-earthmoving machine system

Abstract: Without reliable data on the time of work of construction machines it is impossible to calculate the cost of the investment or the time limit for its implementation. Machine capacity is affected by many factors resulting from both the technical capabilities of a machine (e.g. the engine and bucket capacity) and work environment (e.g. soil loosening and weather conditions). Capacity is also influenced by factors affecting the operator (e.g. health condition, stress, fatigue). Therefore, it is appropriate to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Analyzing formula 8 for the emission factor (EF x ) and formula 9 for the deterioration factor (DF), it can be concluded that the emission value also depends on the age of the machinery, expressed as a proportion of its average lifetime (AF), relative deterioration factor (A) and correction factor (TAF)-both related to the engine class (Stage/Tier) and the type of machine (e.g., excavator, crusher) [39]. The engine load factor i, depends mainly on the operating conditions of the machine [40], and the operator's skills are also significant [41].…”
Section: Technological Processmentioning
confidence: 99%
“…Analyzing formula 8 for the emission factor (EF x ) and formula 9 for the deterioration factor (DF), it can be concluded that the emission value also depends on the age of the machinery, expressed as a proportion of its average lifetime (AF), relative deterioration factor (A) and correction factor (TAF)-both related to the engine class (Stage/Tier) and the type of machine (e.g., excavator, crusher) [39]. The engine load factor i, depends mainly on the operating conditions of the machine [40], and the operator's skills are also significant [41].…”
Section: Technological Processmentioning
confidence: 99%